(untitled) (Jurnal Hortikultura Indonesia, 2023)
Star fruit waste is resulted from fruit thinning or peak harvesting season. It is not used optimally and can cause unpleasant odor around the star fruit orchard. Fruit waste can be used for organic liquid fertilizer and applied in tomato cultivation. The goal of this study is to determine the optimal dosage of liquid organic fertilizer from star fruit waste in order to improve tomato quality and assist sustainable agriculture. The research was carried from August 2021 to March 2022, at Attaqie Farm in Tuban, East Java. The experiment used one-factor treatment in Randomized Block Design with four dose levels of liquid organic fertilizer (LOF) namely 0 ml, 25 ml, 35 ml, and 45 ml LOF per polybag with three replications and each replication used five plant samples. Each treatment is repeated three times and each repetition utilize five plant samples. Fertilization is carried out every week from 2 to 10 weeks after planting (WAP) or for 9 weeks. The study’s findings indicate that applying a 35 ml LOF/polybag is more effective and efficient in achieving the greatest tomato production and quality results in terms of fruit number, fresh fruit weight, and quality. Based on the results of bacterial analysis, the LOF of star fruit waste complies with the specified quality standards. Key words: content of bacteria, stage of tomato maturity, total soluble solids